An attempt to categorize Hungarian community currencies - Eszter Szemerédi (DETUROPE)
Since the emergence of complementary currencies in the 1980s there have been numerous attempts to classify them, despite that the terms local currency, community currency and many others describing place-based monetary tools are not considered similarly by scholars. The local currencies take many forms, and local governments play different roles in their emergence and development. In Hungary there has been an increasing attention and discussion around the idea of implementing these alternative monetary tools. There is a growing number of working complementary currencies in Hungary, but academic research focuses mostly on whether these can contribute to the local development and what kind of effects they have. The aim of this paper is to present a possible categorization of Hungarian complementary currencies based on the role local governments played in their implementation. I evaluate whether these community currencies are effective at first, and attempt to categorize them based on their purpose, association form and their relationships with local governments, with the purpose of increasing awareness for these initiatives in the process of policy-making.